Keterlibatan Metakognitif Siswa dalam Menyelesaikan Soal SPLDV - Candra Wahid Zaenal Abidin; Slamet; Swasono Rahardjo (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2026)
This study examines MTs students’ metacognitive profiles in solving SPLDV word problems. Using a qualitative descriptive case-study design, it involved 30 ninth-grade students of MTs Al-Hidayah Karangsuci Purwokerto who had studied SPLDV. Data were collected through a problem-solving test, semi-structured interviews, and documentation; four students were purposively selected for in-depth analysis. Responses were analyzed through declarative, procedural, and conditional knowledge across Polya’s four problem-solving stages. The findings show varied metacognitive profiles. Students with stronger profiles could identify relevant information, construct mathematical models, choose appropriate strategies, carry out procedures systematically, and check answer plausibility. Students with weaker profiles had difficulty interpreting information, selecting strategies, and evaluating final answers. Procedural knowledge was more visible than declarative and conditional knowledge, while looking back was the weakest stage. These findings suggest that MTs mathematics instruction should explicitly integrate metacognitive questioning, reflective explanation, and answer-checking routines in teaching SPLDV word problems